Close to the Edge: Growth Restrained by the NAD(P)H/ATP Formation Flux Ratio - van Niel, Ed W. J.; Bergdahl, Basti; Hahn-Hägerdal, Bärbel (Frontiers in Microbiology, 2017)
Most fermentative microorganisms grow well under anaerobic conditions managing a balanced redox and appropriate energy metabolism, but a few species do exist in which cells have to cope with inadequate energy recovery or capture and/or redox balancing. Two cases of these species, i.e. the metabolically engineered Saccharomyces cerevisiae enabling it to ferment xylose and Lactobacillus reuteri fermenting glucose via the phosphoketolase pathway, are here used to introduce a quantification parameter to capture what limits the growth rate of these microorganisms under anaerobic conditions. This dimensionless parameter, the cofactor formation flux ratio (RJ), is the ratio between the redox formation flux (JNADH+NADPH) and the energy carrier formation flux (JATP), which are mainly connected to the central carbon pathways. Data from metabolic flux analyses performed in previous and present studies were used to estimate the RJ values. Even though both microorganisms possess different central pathways, a similar relationship between RJ and the specific growth rate (µ) was found. Furthermore, for both microorganisms external electron acceptors moderately reduced the RJ value, thereby raising the µ accordingly. Based on the emerging profile of this relationship an interpretation is presented suggesting that this quantitative analysis can be applied beyond the two microbial species experimentally investigated in the current study to provide data for future targeted strain development strategies.